Factors affecting the use of dental services among Arab children in Israel: a qualitative study - Mohammad Khatib; Yael Ashkenazi; Yoav Loeff; Shlomo Paul Zusman; Lena Natapov (BMC, 2023)
Abstract Background In 2010, Israel reformed its hitherto dominantly privately financed dental services and included preventative and restorative dental care for children in the publicly-funded basket of healthcare services. A survey conducted by Brookdale Institute, found that only 67% of low-income Israeli-Arab children were using the new service (compared to 85% of Jewish children) while the majority of others continue using privately funded services. The aim of this study is to explore and explain Israeli-Arab children's low utilization of publicly-funded preventive and restorative dental care. Methods A qualitative study designed to describe and understand the parents' motivations and choices. As a preliminary stage, eight semi-structured interviews were conducted with directors of HMO dental departments and Israeli-Arab dentists. In the second stage, ten one-on-one interviews with parents, and five focus group discussions with 55 parents held on February-March 2017. All discussions in the focus groups were conducted in Arabic and each group was moderated by one of the research team accompanied by another person who documented and recorded the discussion. All interviews and discussions were recorded, transcribed in full and translated into Hebrew. Results The prevalent attitude is that one goes to the dentist only when there is a serious problem. The importance of preventive care is not appreciated. A childhood fear of the drill is very remembered and passed onto the children. Social and cultural factors such as kinship with service providers (GPs and dentists) influence the choice and utilization of health services. Economic barriers are still existing since even the small co-payment is daunting to low-income parents of large families. Provision of the public service is inadequate in some Arab villages. Conclusions The extension of Israel's National Health Insurance Law's basket of services to include dental care for children, while important, is not sufficiently embraced by Israeli Arab children. The remaining barriers include poor living conditions, low educational level that requires very clear sharing of information about the new service, and the resistance of cultural and social traditions. Public dental services providers should focus on conveying relevant oral health messages to the parents too, either through their children or directly.